Characteristics of Students as Digital Natives: Opportunities and Challenges for the Guidance and Counselling Profession - Andre Julius; Muthahharah Thahir; Dwi Risma Sari (Universitas Muhammadiyah Mataram, 2026)
Understanding the student's character is key to the success of counselling services. It is not uncommon for guidance and counselling teachers to receive requests from clients due to differences in perspectives between generations. Generation Z and Alpha are the clients targeted by guidance and counselling services today, so that in addition to understanding the problems, guidance and counselling teachers must also understand how to view these digital native generations. This study aims to conceptually examine the characteristics of Generation Z and Alpha as clients, while also identifying the opportunities and challenges facing the guidance and counselling profession. The study was conducted using a systematic literature review method specifically using SINTA and SCOPUS indexed articles as references. The results show that Generation Z and Alpha as clients have a high attachment to digital technology, good awareness of mental health issues, but are vulnerable in communication, problem-solving, and social relationships. These characteristics encourage the guidance and counselling profession to develop flexible, accessible, and technology-based services, but at the same time demand a transformation of paradigms, competencies, and counselling practices to remain client-cantered. The main challenge lies in meaningful counselling relationships, as well as strengthening identity and belonging in clients.